Emerging Concepts in Fibroblast Biology and Progressive Pulmonary Fibrosis - Singh, Priyanka; Edjah, Shanda; Shi, Wei; Madala, Satish K. (Seminars in Respiratory and Critical Care Medicine, 2025)
Pulmonary fibrosis is characterized by scarring and thickening of the lung parenchyma due to excessive deposition of collagen and other extracellular matrix (ECM) proteins. This leads to disruption of gas exchange areas and ultimately respiratory failure, a pathology shared across multiple interstitial lung diseases (ILDs). Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive ILD characterized by exertional dyspnea, dry cough, and restrictive lung defects. Clinical progression is marked by worsening lung function, declining exercise tolerance, and hypoxemia. High-resolution computed tomography in IPF typically shows reticular opacities and honeycombing, predominantly distributed in the subpleural regions and lower lobes of the lungs. The disease course is variable, with episodes of acute exacerbation associated with high mortality. Myofibroblasts and fibroblasts are central drivers of fibrogenesis through uncontrolled proliferation, migration, survival, senescence, myofibroblast differentiation, and ECM production. Myofibroblasts represent a heterogeneous population in both origin and function, arising from diverse precursor cells, including lung resident fibroblasts, endothelial cells, and mesothelial cells, and are shaped by tissue-specific niches. Persistent activation of (myo)fibroblasts is sustained by a complex network of profibrotic growth factors and their downstream transcriptional regulators. In this review, we comprehensively examine the cellular origins and molecular pathways underlying fibroblast activation, with an emphasis on mechanistic insights that may inform the development of targeted antifibrotic therapies to attenuate disease progression and improve patient outcomes.
Keywords: idiopathic pulmonary fibrosis; fibroblast; collagen; lung; extracellular matrix